Жіночі портрети Лівобережної України в колекції Національного музею історії України. Кінець XVIII - початок ХІХ ст. - Суховарова-Жорнова, О. (Спеціальні історичні дисципліни: питання теорії та методики, 2007)
Автор статьи впервые в украинской иконографии исследует и анализирует женские портреты Левобережной Украины конца ХVIII – начала XIX вв., хранящиеся в Национальном музее истории Украины. Доказывается ценность данного исторического источника и его информационный потенциал. The first in Ukrainian iconography the author of article researches and makes analyze the woman’s portraits in the end XVIII – beginning XIX centuries which belong to the part of left Ukraine in ХVІІІ – ХІХ centuries by collection the National museum of history of Ukraine. Here demonstration the value this historical sources and information potential.